Vegetais do Oxfordiano (Lusitaniano) de Leiria - Pais, João (2008)
Some plant fossils from Oxfordian (Lusitanian) beds near Leiria (Portugal) are described: Equisetites sp., Todites falciformis PAIS, Coniopteris cf. murrayana (BRONGN.), Nilssonia cf. kendalli HARRIS, Otozamites sp., Pterophyllum sp. and Elatides cf. curvifolia DUNKER. Comparisons are established with similar plant associations from Upper Jurassic of Yorkshire and cabo Mondego (Portugal).